Comprehensive opportunity assessment using commercial and moral intensities - Richard J. Arend (Administrative Sciences, 2021)
We propose a partial theory explaining the processing of opportunities by individuals in organizations, specifically for opportunities with both commercial and moral significance (measured as intensities). The goal of such theorizing is to identify and analyze the range of interactions that the ethical and economic impacts of an opportunity can have so that managers can make better decisions on their exploitation and modification. We explain why and how there is variance in the processing of the ideas behind such opportunities as caused by their moral and commercial intensities. We explain the likely interactions between those two intensities, and when they occur and what can result. Doing so complements work in social entrepreneurship and corporate social responsibility by filling the gaps of the possible combinations of economic and ethical interactions. We provide these explanations by leveraging a precedent model that had adapted a standard knowledge-processing method to ethical decision-making issues. The explanations resonate because our model leverages the traditional textbook entrepreneurship opportunity evaluation criteria to provide a holistic view of an underlying idea's commercial intensity, a view that aligns with the driving assumption that the focal decision-makers are boundedly rational.
Keywords: 350; commercial intensity; decision-making process; moral intensity; opportunity assessment; social entrepreneurship